1999
DOI: 10.1097/00007890-199904270-00013
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Kidney Transplantation From High-Risk Donors Is Determined by Both Structure and Function

Abstract: Calculated donor CrCl and donor vascular pathology predict recipient graft function and may be helpful in selecting high-risk donors for single kidney transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
142
0
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(155 citation statements)
references
References 24 publications
6
142
0
7
Order By: Relevance
“…Nevertheless, numerous studies have shown that graft function and survival are affected by different donor nonimmunological factors, such as donor age, gender, race, size, and mode of death (1)(2)(3)(4). Fewer studies have analyzed the influence of donor kidney function on subsequent graft function but this influence has been reported as significant (5), modest (6,7) or even nonsignificant (3). In these studies kidney or graft function was most commonly estimated by creatinine clearance, as calculated by the Cockcroft-Gault formula, and the influence of donor factors was examined on graft function at multiple timepoints (3,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, numerous studies have shown that graft function and survival are affected by different donor nonimmunological factors, such as donor age, gender, race, size, and mode of death (1)(2)(3)(4). Fewer studies have analyzed the influence of donor kidney function on subsequent graft function but this influence has been reported as significant (5), modest (6,7) or even nonsignificant (3). In these studies kidney or graft function was most commonly estimated by creatinine clearance, as calculated by the Cockcroft-Gault formula, and the influence of donor factors was examined on graft function at multiple timepoints (3,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Karpinski és mtsai 34 donor vesebiopsziás mintáit vizsgálták az alábbi szempontok alapján: glomerulosclerosis, interstitialis fibrosis, tubularis atrophia és vascularis eltéré-sek [25]. Ezen a vizsgálaton alapszik a Remuzzi (Pirani) -score is, amely a szövettani eltéréseket pontozva három fő csoportba sorolja a veséket aszerint, hogy mennyi életképes nefron található bennük [26].…”
Section: Eredeti Közleményunclassified
“…Outcomes of ECD kidney transplantation are improved when a pre-implantation biopsy of the donor kidney is evaluated using the scoring system introduced by Karpinski and colleagues (Karpinski et al, 1999) . Using this system, donor renal pathology is scored from 0 to 3 (none to severe disease) in 4 areas: glomerulosclerosis, interstitial fibrosis, tubular atrophy, and vascular disease.…”
Section: Role Of Kidney Biopsymentioning
confidence: 99%